Parasitism by Amblyomma ovale on domestic dog in the central region of the state of Rio Grande do Sul, Brazil - Julia Somavilla Lignon; Thiago Fernandes Martins; Silvia Gonzalez Monteiro (Acta Scientiarum. Animal Sciences, 2023)
Ticks are obligate ectoparasite arthropods of the class Arachnida distributed worldwide and can parasitize many animals. They constitute one of the most important groups of vectors of infectious diseases, including zoonoses. The objective of this study was to report the parasitism by Amblyomma ovale Koch, 1844 in a domestic dog (Canis lupus familiaris Linnaeus, 1758) in Santa Maria, in the central region of the state of Rio Grande do Sul, Brazil. Two specimens of ectoparasites found on a domestic dog, living in a rural property, were sent to the Laboratory of Veterinary Parasitology at the Federal University of Santa Maria for taxonomic identification. The two specimens found were classified as adult male and female of A. ovale. Through this study, the parasitism of this species is reported for the first time in the central region of the state of Rio Grande do Sul, Brazil, in a domestic dog, allowing the infestation and transmission of diseases to humans.